2016
DOI: 10.1093/bja/aew307
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of renal perfusion and oxygen metabolism to predict postoperative acute kidney injury in neonates and infants after cardiopulmonary bypass surgery

Abstract: Monitoring of renal oxygen metabolism allows early prediction of AKI in infants after cardiac surgery. In contrast, renal resistive index does not allow prediction of AKI after neonatal palliation with aortopulmonary shunt establishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 51 publications
(77 reference statements)
0
21
0
Order By: Relevance
“…Near-infrared spectroscopy allows for the continuous assessment of regional tissue oxygenation (rSO 2 ), and is believed to reflect renal rSO 2 when placed on the flank overlying the kidney. While some studies have observed an association between prolonged periods low perioperative renal rSO 2 and AKI after congenital cardiac surgery (911), other studies have failed to show an association (12, 13). Interestingly, although the study by Hazle, et al did not find an association between prolonged low renal rSO 2 and creatinine-based AKI after infant cardiac surgery, they did observe an association between renal rSO 2 and higher postoperative NGAL and interleukin-18 levels, suggesting an association between renal rSO 2 and kidney injury by more novel indicators (13).…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared spectroscopy allows for the continuous assessment of regional tissue oxygenation (rSO 2 ), and is believed to reflect renal rSO 2 when placed on the flank overlying the kidney. While some studies have observed an association between prolonged periods low perioperative renal rSO 2 and AKI after congenital cardiac surgery (911), other studies have failed to show an association (12, 13). Interestingly, although the study by Hazle, et al did not find an association between prolonged low renal rSO 2 and creatinine-based AKI after infant cardiac surgery, they did observe an association between renal rSO 2 and higher postoperative NGAL and interleukin-18 levels, suggesting an association between renal rSO 2 and kidney injury by more novel indicators (13).…”
Section: Introductionmentioning
confidence: 99%
“…Further, clinical management of AKI in preterm infants is challenging and often ineffective due to therapeutic limitations to renal replacement therapy (ie, dialysis) in this population; therefore, early recognition and prevention may enhance the efficacy of current therapeutic approaches or limit additive injury from pathologic or iatrogenic sources 12. Continuous renal NIRS monitoring may provide an early warning indicator for potential or actual renal hypoperfusion, which is supported by recent studies 9–11,15–22…”
mentioning
confidence: 87%
“…However, NIR technology is not used during cardiac surgery for the monitoring of kidney function in clinical practice, yet it could serve as a possible solution for the earlier detection of CSA-AKI [ 45 , 46 , 61 ]. In multiple studies [ 50 , 55 , 58 , 61 , 62 , 63 ], CSA-AKI has been linked to lower renal rSO 2 values both intra-operatively (i.o.) and during the first 48 h postoperatively (p.o.)…”
Section: Kidney Diseasesmentioning
confidence: 99%